UTILIZING CRITICAL DISCOURSE ANALYSIS FOR AUTHENTIC MATERIAL AND CROSS-CULTURAL CONTENT: APPLIED LINGUISTICS AND HUMANISTIC WORK - Hasan Khalawi; Samsul Hadi (LPPM Press STKIP PGRI Pacitan, 2017)
To date, the critical thinking and interpretation is such a constraint for that globalized life and culture. This shift was affected by the maturity of human and their cultures. Alpha generation, referring to generation theory, is that mentioned period of being critical, complex, and liable to search the truth through scientific reasoning and logical interpretation. For that reason, this research is aimed at revealing kind of Critical Discourse Analysis (CDA) devices which are able to uncover the hidden meaning; and how those critical discourse analysis devices are applied to cross-cultural content and humanistic values using authentic materials. Based on the search of the researcher, there is still minimal research and writing pertaining to this issue. Then, this research hopefully becomes the significant credit to English education rehearsal and development. This research is naturally pseudo mixed methods in the paradigm of Applied Linguistics. The data source is from the authentic material (English magazine or newspaper), while the process of the research data collection is the adaptation of George (2008) which is finally analyzed using Spradley analysis (1980). Based on the need of Alpha generation, CDA in the framework of Applied Linguistics is hopefully providing such contribution and benefits for English education in Indonesia. Based on the research findings, the uncovered phenomena are as follows: (1) the devices of the Critical Discourse Analysis (CDA) to be applied in the framework of Applied Linguistics (AL) are the biases of (a) power; (b) culture; (c) identity; (d) ideology; (e) interest; (f) politics; (g) intertextuality; (h) value; (i) subjectivity; and (j) agenda; (2) the critical discourse analysis can be applied both in the research and teaching strategy by analyzing the discourse in the authentic material to uncover the phenomena; (3) worldview of people is the source of intellectual and social activity. So, by employing the CDA and AL, the teacher or the researcher will recognize whether or not the worldview is good for the Islamic worldview and the local wisdom in the Eastern country.